The end of television: David Hall’s 1001 TV Sets (End Piece) - Ball, Steven (Moving Image Review & Art Journal (MIRAJ), The, 2013)
Ambika P3, London 16 March – 22 April 2012
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9taXJhai4yLjEuMTMyXzU